1982
DOI: 10.1055/s-2007-1019052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Streptozotocin Diabetes on the Pituitary-Testicular Axis in the Rat

Abstract: enzyme cleaving the side-chain of cholesterol (rate limiting step in steroidogenesis) was considerably reduced in the diabetic state (59%, p < 0.002) and insulin treatment restored it to even supranormal levels (not significant). Our findings suggest that insulin may play a physiological and differential role in regulating the secretory activity of the anterior pituitary. The insulin is needed for normal LH and prolactin release and Leydig cells function but its role in FSH release and Sertoli cells function i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Two hypotheses may be discussed: (1) is it possible that decreased epididymal ABP levels are due to decreased serum FSH levels? Serum FSH concentrations have been reported to be decreased in streptozotocin-diabetic animals [2], but this finding has not been confirmed by other authors [3,7]. FSH has been proposed to enhance both testicular and epididymal ABP concentrations [8,9,11] as well as the ABP production by cultured Sertoli cells from immature rats [12].…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Two hypotheses may be discussed: (1) is it possible that decreased epididymal ABP levels are due to decreased serum FSH levels? Serum FSH concentrations have been reported to be decreased in streptozotocin-diabetic animals [2], but this finding has not been confirmed by other authors [3,7]. FSH has been proposed to enhance both testicular and epididymal ABP concentrations [8,9,11] as well as the ABP production by cultured Sertoli cells from immature rats [12].…”
Section: Discussionmentioning
confidence: 42%
“…Numerous studies have demonstrated impairment of fertility [1] and testicular endocrine function [1-4] to be late complications of streptozotocin-treated hypoinsulinaemic, hyperglycaemic male rats. In addition to reports on defective spermatogenesis [5][6] and indications of disturbances of pituitary gonadotropin secretion [1][2][3][5][6][7], dysfunction of the Leydig cells resulting in diminished testosterone formation in these diabetic animals seems to be the most extensively investigated problem in this field [1][2][3][4]. …”
mentioning
confidence: 99%
“…Various reports have suggested that the diminished sexual behavior in STZ-induced diabetic rats is related to changes in hypothalamic-pituitary gonadal axis (27,29). However, gonadectomy did not change the urethrogenital reflexes, suggesting that androgen changes are unlikely as the cause of the sexual dysfunction in this model (10).…”
Section: Discussionmentioning
confidence: 91%
“…There is a wide disparity regarding the effects of insulin treatment on gonadotrophin levels in diabetic individuals with reports ranging from a total recovery of both LH and FSH (Seethalakshmi et al 1987), to the recovery of just one (Perez Diaz et al 1982, Hutson et al 1983, Benitez & Perez Diaz 1985, Sudha et al 2000 or even the absence of effects (Steger & Kienast 1990), suggesting that testicular function regulation is the result of a complex process in which several players are involved. Other studies have explored these aspects in more detail, and insulin treatment was observed to totally reverse all parameters of pulsatile LH secretion, which were reduced in diabetic rats and, at least partially, due to a decreased responsiveness of the pituitary to GnRH (Dong et al 1991).…”
Section: Pre-testicular Levelmentioning
confidence: 99%
“…In early experiments, it was shown that untreated diabetes caused a reduction in serum LH, testosterone levels and steroidogenic activity and that these parameters were restored by insulin treatment (Tesone et al 1976, Murray et al 1981, Perez Diaz et al 1982, Benitez & Perez Diaz 1985, raising the question on whether the effects of insulin are directly in the testis or induced through alterations in LH secretion. Furthermore, it was observed that Leydig cells' LH receptors were decreased in diabetic rats, though the binding capacity was restored after insulin administration (Charreau et al 1978).…”
Section: Testicular Levelmentioning
confidence: 99%